Financial Report Analysis to Assess The Performance of PT. Goto Gojek Tokopedia Tbk (Goto) - Aliana Lukman, Alpia (Syntax Corporation, 2025)
This study aims to analyze the financial statements of PT. Goto Gojek Tokopedia Tbk (GOTO) to assess the company's performance from 2020 to 2023. In the increasingly developing digital era, GOTO as an integrated technology platform plays an important role in the e-commerce and on-demand service industry in Indonesia. This analysis includes an evaluation of various financial aspects, including liquidity ratios, solvency, profitability, and activity, as well as a comparison with similar companies in the technology sector. The results of the analysis show that although GOTO faces challenges in maintaining profitability, the company has managed to show significant revenue growth and improve its liquidity position. In addition, an assessment of investment spending and expansion strategies shows GOTO's commitment to maintaining a competitive advantage in the market. This study is expected to provide insight for investors and stakeholders regarding the potential and challenges faced by GOTO in achieving long-term sustainability.